2011
DOI: 10.1063/1.3641638
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen [N]-incorporated ZnO piezoelectric thin films and their application for ultra-small film bulk acoustic wave resonator device fabrication

Abstract: Nitrogen [N]-incorporated ZnO films with columnar grains of a preferred c-axis orientation were deposited on p-Si (100) wafers, using an RF magnetron sputter deposition technique. For the N incorporation into the ZnO films, an N 2 O gas was used as a doping source and also various process conditions such as N 2 O gas fraction and RF power were applied. Besides, some of the ZnO films were treated with the post annealing process. And then, the micro-structural characteristics of the N-incorporated ZnO films were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Wurtzite phase ZnO has versatility in many applications including ultraviolet (UV) light emitting diodes, UV photo detectors, solar cell windows, gas sensors, acoustic wave resonator devices, transparent conductors, and transparent thin film transistors (TFTs) [3,4]. Particularly, ZnObased TFTs are well suited for the active matrix liquid crystal displays (AMLCDs) or entirely transparent displays [5][6][7][8] because of very low opacity, wide band gap (3.37 eV), binding energy (60 meV), and higher intrinsic mobility.…”
Section: Introductionmentioning
confidence: 99%
“…Wurtzite phase ZnO has versatility in many applications including ultraviolet (UV) light emitting diodes, UV photo detectors, solar cell windows, gas sensors, acoustic wave resonator devices, transparent conductors, and transparent thin film transistors (TFTs) [3,4]. Particularly, ZnObased TFTs are well suited for the active matrix liquid crystal displays (AMLCDs) or entirely transparent displays [5][6][7][8] because of very low opacity, wide band gap (3.37 eV), binding energy (60 meV), and higher intrinsic mobility.…”
Section: Introductionmentioning
confidence: 99%
“…Among the group V elements, the ionic size of N is most closely comparable to that of oxygen (O) in terms of radius (r N 3À ¼ 1:68 Å , and r O 2À ¼ 1:38 Å ), and helps to create acceptors (e.g., N substitutes for O sites in the ZnO lattice [N O ]); these acceptors compensated considerably for native donors in ZnO (e.g., Zn i , V O , or H). 8,9,[14][15][16] In this study, we intended to take full advantage of this N-compensatory doping, 26 which is expected to modulate the inherently n-typebiased ZnO conductivity more effectively and make it a more electrically resistive n-type material.…”
Section: à3mentioning
confidence: 99%
“…Various studies have shown that the crystalline structure of AlN films can be improved through post-deposition plasma, laser, or rapid thermal annealing (RTA) treatment [12, 17, 18]. Lee also reported that an excellent return loss of the solidly mounted resonator-type film bulk acoustic wave resonator devices were observed after the post annealing process [19]. High crystallinity AlN films were obtained by modulating the growth temperature and thermal annealing conditions.…”
Section: Introductionmentioning
confidence: 99%